UNDERSTANDING PARAGRAPH AND THREE PHASES IN READING COMPREHENSION - Eka Sustri Harida (Institut Agama Islam Negeri (IAIN) Padangsidimpuan, 2016)
Reading Comprehension is a mental process when the readers try to understand the meaning in the text by interpreting what have been read in order to find the idea given by the writers. The readers should pay attention for some aspects such as how they understand the words and the information from the text, understanding main ideas and details, and be able to make conclusion. Understanding three phases in reading is important to prepare reading strategies and the purpose of reading; it needs to help the readers understand the text that they read. Further, in understanding paragraph, then readers must also apply the three phases in order to make them able in finding ideas in the paragraph. Understanding paragraph and the phases are done to make the readers able in taking the meaning from the text.